Building a green economy : perspectives from ecological economics - Richardson, Robert B. (Michigan State University Press, 2013)
The first decade of the twenty-first century has been characterized by a growing global awareness of the tremendous strains that human economic activity place on natural resources and the environment. As the world's population increases, so does the demand for energy, food, and other resources, which adds to existing stresses on ecosystems, with potentially disastrous consequences. Humanity is at a crossroads in our pathway to future prosperity, and our next steps will impact our long-term sustainability immensely. In this timely volume, leading ecological economics scholars offer a variety o.